Concurrent training in team sports: A systematic review - Seipp, D.; Quittmann, O. J.; Fasold, F.; Klatt, S. (International Journal of Sports Science & Coaching, 2023)
Background: Concurrent strength and endurance training could interfere with adaptation, which primarily affects long-term strength development. However, so far, research on this theme has rarely focused on ways to optimize concurrent strength and endurance training in team sports.